Easy peel off nail polishing - Lin, Hongying (2018)
Nail polish can be utilized on fingernails and toenails; primarily by ladies. It is normal for young ladies to "paint their fingernails." People additionally go to salons to complete their nails. It is exceptionally trendy. The nail polish mainly consists of two components, one is a solid component which is color, and the other one is a liquid solvent component. Nitrocellulose compounds dissolved in butyl acetate or ethyl acetate liquids. These two components will cause nail if is in good coverage, uniformity, brightness, drying time, scratch resistance, impact resistance, resistance to liquids, odor and so on. The people’s requirement of nail polish changes and enhance as the time changes. In this project, the new nail polish to be tested out and experiment with engineering polymers for nail polish to obtain a low cost easily removable nail coloring method with a shorter drying time and easy to remove from the nail without applying polish remover. In this “busy” world, we have the limit timing to do our own lovely thing, therefore, the timing is the main concern to those beautiful women. In the life, the people’s pursuit is novelty, freshness, and diversity, therefore the nail polish easy to remove from the nail without applying polish remover and apply new nail polish on the nail at the next day or next few days. Moreover, cosmetic and beauty industry is growing day by day and good chances are present in this in upcoming future.